2015
DOI: 10.2319/122113-936.1
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of clinical complications during orthodontic treatment with either a removable mandibular acrylic splint Herbst or with a cantilever Herbst

Abstract: On average, approximately 2.5 complications per patient were reported. Most patients had a maximum of three complications during Herbst treatment. Herbst appliance type (RMS or HC) and fixation mode (crowns or Grip Tite bands) did not influence the number of complications. The PMA (without screws) telescopic system seemed to be more reliable (regarding the number of complications) than Dentaurum type 1, regardless of the appliance design (RMS or HC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 7 publications
(6 reference statements)
0
20
1
1
Order By: Relevance
“…The proportion of Herbst appliance complications has been reported to be up to 88 % during treatment time or the observation period [16]: A recent study of the complication rate for two differently attached Herbst appliances reported an incidence of complications of 85.3 % during treatment with a crown-supported appliance, and 88.0 % in subjects with an appliance that was crown-supported in the maxilla, but splint-supported in the mandible [16]; Silva et al calculated a mean complication rate of 2.5 events per patient, with no statistically significant difference between the two appliances [16]. However, their calculated complication rate also included smaller complications not resulting in an interruption of a forward guidance of the mandible, such as gingiva irritations provoked by the Herbst appliance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The proportion of Herbst appliance complications has been reported to be up to 88 % during treatment time or the observation period [16]: A recent study of the complication rate for two differently attached Herbst appliances reported an incidence of complications of 85.3 % during treatment with a crown-supported appliance, and 88.0 % in subjects with an appliance that was crown-supported in the maxilla, but splint-supported in the mandible [16]; Silva et al calculated a mean complication rate of 2.5 events per patient, with no statistically significant difference between the two appliances [16]. However, their calculated complication rate also included smaller complications not resulting in an interruption of a forward guidance of the mandible, such as gingiva irritations provoked by the Herbst appliance.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, consideration of treatment intervals without severe complications is useful, in order to characterize the robustness of a fixed, functional appliance. This information is often not directly manifest from the literature [12–14, 16], but can be calculated by multiplying numbers of study patients by mean treatment time and then dividing this by the numbers of severe complications that occurred. Though this kind of calculation probably averages repeated events over the whole sample, which may not necessarily be related to the appliance itself (such as with repeated fractures in single patients, as was seen in this study, but also others - see Hägg et al, who reported on one subject who was affected six times by a fracture) [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, mandibular splint shows decreased resistance. 11 Apart from its usefulness, it has many shortcomings. In our study, we have noticed various complications, such as screw loosening, crown debounce, distortion of rod, fracture of crown, breakage of low splint, breakage of pivot, transpalatal arch breakage, cantilever inducing gingival lesion, cantilever inducing palatal lesion, lesion on cheek due to long rod, and transpalatal arch breakage.…”
Section: Discussionmentioning
confidence: 99%